Towards Strengthening of the OSCE Effectiveness in Responding to International and European Security Challenges - Igor Shcherbak (Международная аналитика)
The author is accentuating the importance of improving effectiveness of the OSCE’ crisis management in the conditions of erosion of strategic stability on the European continent in the result of unprecedented worsening of relations between Russia and the West. Special attention is devoted to the modernization of the OSCE’s crises management potential and maintaining dialogue between the West and Russia, including by creation of consultative platform in the framework of the OSCE to discuss emergencies. The author proposed adoption of several confidence-building measures aimed at restoration of dialogue and finding the way to settle the crises situations. In this context important role could be given to establishing complex peacekeeping missions under the auspices of the OSCE.